2019
DOI: 10.3390/ijms20030731
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-Mediated Pendrin Transcriptional Regulation in Airway and Esophageal Epithelia

Abstract: Pendrin (SLC26A4), a Cl−/anion exchanger, is expressed at high levels in kidney, thyroid, and inner ear epithelia, where it has an essential role in bicarbonate secretion/chloride reabsorption, iodide accumulation, and endolymph ion balance, respectively. Pendrin is expressed at lower levels in other tissues, such as airways and esophageal epithelia, where it is transcriptionally regulated by the inflammatory cytokines interleukin (IL)-4 and IL-13 through a signal transducer and activator of transcription 6 (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 172 publications
(223 reference statements)
0
11
0
Order By: Relevance
“…premature stop codon mutations), activation of TMEM16A could also restore Cl − /HCO 3 − efflux. As CFTR may regulate other channels and transporters like the epithelial Na + channel or pendrin in surface epithelial cells [36,40,41], TMEM16A activation may not fully replace CFTR. However, this study and previous work [6] suggest TMEM16A can support levels of Cl − and HCO 3 − efflux from serous cells equivalent to CFTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…premature stop codon mutations), activation of TMEM16A could also restore Cl − /HCO 3 − efflux. As CFTR may regulate other channels and transporters like the epithelial Na + channel or pendrin in surface epithelial cells [36,40,41], TMEM16A activation may not fully replace CFTR. However, this study and previous work [6] suggest TMEM16A can support levels of Cl − and HCO 3 − efflux from serous cells equivalent to CFTR.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 inflammation was suggested to upregulate Cl − /HCO 3 − exchanger pendrin in airway surface epithelial cells [40,41]. We examined if NPY or IL-13 induced altered expression of pendrin or Cl − channels in primary serous cells, perhaps shifting serous cells away from CFTR toward a more TMEM16A-and/or pendrin-dominated secretory phenotype.…”
Section: Npy and Vip Have Opposing Effects On CL − And Hcomentioning
confidence: 99%
“…Our results showed that IL‐11 could potentially be used as an independent prognostic factor for EAC. Among the interleukin family, secretion of IL‐33 in esophageal epithelial cells has been reported to prompt the occurrence of gastroesophageal reflux diseases and lead to Barrett esophagus; 31 IL‐4, IL‐13, 32 IL‐1β 33 and IL‐6 34 contributed to increased secretion of esophageal mucosa in patients with Barrett's esophagus, and IL‐11 contributed to esophageal squamous cell carcinoma progression and its aggressiveness 35 . Nonetheless, to date, no study has reported the role of IL‐11 in EAC, and our study fills this gap and confirms the potentially important role of it in EAC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of secreted mucins could result from the ability of CSs to reduce GCH and could account for the reduction of mucus production and rhinorrhea [59]. The histological features of sinus mucosal lesions in CRS are the large number of inflammatory cell infiltration and cytokine release [60], particularly neutrophils [52,61,62], which were reported to be associated with mucosal remodeling. Sampson et al [63] showed that neutrophils played a role in remodeling by secreting recombinant mediators (such as MMPs and TGF-β) [64].…”
Section: Regulation Of Mucins In Crsmentioning
confidence: 99%